PERFORMATIVITAS IDENTITAS GENDER DAN SEKSUALITAS DALAM NOVEL IMARAH YAKUBIAN KARYA ALA AL-ASWANI - Khurosan, Herpin Nopiandi (MIMESIS, 2020)
This study examines aspects of the performativity of gender identity and sexuality in the novel Imarah Yakubian by Alaa al-Awani. Through Judith Butler's theory of performativity, the author examines how the identity and gender sexuality performativity of the characters and how the attitude of the characters in the novel Imarah Yaqubian in responding to the dominance of heteronormativity.The results showed that Egyptian society which was dominated by heteronormativity ideology gave birth to the marginalization of homosexuals. Individuals who have 'deviant' gender and sexuality tendencies respond to compliance, negotiation, or resistance. Compliance in the novel IY was shown by Abduh by positioning and publicly showing himself as what was considered normal by the general public. The moderate-negotiate response was demonstrated by Hatim al-Rashid's figure by showing the things that were acceptable to the public in the public sphere and showing what he wanted in the private sphere.